An experimental study on RC beams shear-strengthened with Intraply Hybrid U-Jackets Composites monitored by digital image correlation (DIC) - Cakir, Ferit; Aydin, M. Raci; Acar, Volkan; Aksar, Bora; Akkaya, Hasan Cem (ELSEVIER SCI LTD, 2023)
Reinforced concrete (RC) beams are commonly strengthened using steel stirrups, but these materials have limitations such as added weight and susceptibility to corrosion. Fiber-reinforced polymers (FRPs) offer a promising alternative to steel stirrups with high mechanical performance, low density, and resistance to corrosion and chemicals. In particular, Intraply Hybrid Composites (IRCs), which comprise multiple fibers oriented in different directions within a single matrix, have recently gained attention in the construction industry. Cakir et al. [1] investigated the use of three types of IRCs (Aramid-Carbon (AC), Glass-Aramid (GA), and Carbon-Glass (CG)) for strengthening 2-meter-long RC beams (the ratio of shear span (a) to effective depth (d) equals 3 (a/d = 3)) against shear fractures. In this study, the effects of these IRCs on the shear strength of 1.5-meter-long RC beams (a/d = 2) without transverse reinforcement were examined. In this scope, four-point bending tests were conducted on the beams after U-shaped IRC strengthening, and the impact of IRCs on shear strength was evaluated using both digital image correlation and classical measurement equipment such as strain gauges and linear variable differential transducers. The maximum load measured in RC1.5 was 194.50 kN, while the ultimate load capacity reached 265 kN in AC1.5, 246 kN in GA1.5, and 229 kN in CG1.5 after strengthening, representing increases of 36%, 26%, and 18%, respectively, compared to RC1.5. Additionally, the maximum mid-span deflections were determined as 30.40 mm, 16.10 mm, 22.20 mm, and 36.40 mm for RC1.5, AC1.5, GA1.5, and CG1.5, respectively. Moreover, the experimental results were compared with the predictions obtained from the international codes. It should be noted that the failure modes of RC beams are directly affected by the type of IRCs used, highlighting the significant contribution these materials can make to the structural behavior of RC beams.
Keywords: Reinforced concrete beams; Fiber-reinforced polymers; Intraply hybrid composites; Shear strengthening; Digital image correlation; Mechanical tests; REINFORCED-CONCRETE BEAMS; PERFORMANCE; BEHAVIOR; Mechanics; Materials Science